Indigenous peoples struggle for communal lands in Sundargarh, India - Tharu, Prem Singh (Technical Centre for Agricultural and Rural Cooperation, 2018)
Throughout the world, indigenous peoples live on ancestral land and territories, governed by their cultural and traditional norms and values. Their lives and livelihoods are heavily dependent on natural resources and these are managed in a way which is similar to that envisioned by the Sustainable Development Goals (SDG). In recent years, however, governments and corporations have been grabbing and exploiting indigenous community land and establishing industries in these resource-rich areas – for example in Odisha, India. In the Telighana village of Sundargarh, indigenous people are struggling to protect their land, as their rights are not recognised. Their fight is an example and a source of inspiration.